Visual nutrition analysis: leveraging segmentation and regression for food nutrient estimation - Zhao, Yaping; Zhu, Ping; Jiang, Yizhang; Xia, Kaijian (Frontiers in Nutrition, 2024)
IntroductionNutrition is closely related to body health. A reasonable diet structure not only meets the body’s needs for various nutrients but also effectively prevents many chronic diseases. However, due to the general lack of systematic nutritional knowledge, people often find it difficult to accurately assess the nutritional content of food. In this context, image-based nutritional evaluation technology can provide significant assistance. Therefore, we are dedicated to directly predicting the nutritional content of dishes through images. Currently, most related research focuses on estimating the volume or area of food through image segmentation tasks and then calculating its nutritional content based on the food category. However, this method often lacks real nutritional content labels as a reference, making it difficult to ensure the accuracy of the predictions.MethodsTo address this issue, we combined segmentation and regression tasks and used the Nutrition5k dataset, which contains detailed nutritional content labels but no segmentation labels, for manual segmentation annotation. Based on these annotated data, we developed a nutritional content prediction model that performs segmentation first and regression afterward. Specifically, we first applied the UNet model to segment the food, then used a backbone network to extract features, and enhanced the feature expression capability through the Squeeze-and-Excitation structure. Finally, the extracted features were processed through several fully connected layers to obtain predictions for the weight, calories, fat, carbohydrates, and protein content.Results and discussionOur model achieved an outstanding average percentage mean absolute error (PMAE) of 17.06% for these components. All manually annotated segmentation labels can be found at https://doi.org/10.6084/m9.figshare.26252048.v1.